SIMULASI LAMPU BERJALAN DAN HITUNGAN MUNDUR BERBASIS MIKROKONTROLER AT MEGA32 - Haryanto, Nanang (Siscode, 2013)
Growing of technology is more modern from time to time in this case can be ilustrate like a microcontroller AT Mega32. Microcontroller is a part of configuration control system that using for process of memory control even can program to save of instruction with the spesific rules and to implement of special function like a logic functio, timer and counter. Methode of work is checking of input condition or a program. A running light and a count down made with a simulation using a software of proteus. This design purpose to more understanding a function of minimum work of a microcontroller. It is easy to make a simulation circuit using a proteus software. It just to contact with pins of seven segment light to port of IC output. After a circuit of form the next step is make a program use abasic compiler so the program that have been made can simulated to simulation circuit. Base on practice, that have been done this simulation work fit to the instruction. The work of this equipment is start from reading a program in cronological order where the red lamp of seven segment will turn on from 20 to 00 and after that the green lamp on alternately from 9 to 0. At the time red and green lamp are turn on, the running light also turn on. Keyword : simulation, running light, count down,microntroller AT Mega32